Penguatan Ecological Citizenship Kelompok Anti Tambang Pasir dalam Pemenuhan HAM Lingkungan pada Masyarakat (Studi Kasus Tambang Pasir Desa Selok Awar-Awar Lumajang) - Kemal Pasha kemal; Raden Roro Nanik Setyowati (Kajian Moral dan Kewarganegaraan, 2023)
This study explains the real action of anti-mining groups by strengthening Ecological Citizenship, in dealing with environmental damage and handling it by anti-mining groups. The purpose of this study is to describe the strengthening of the Ecological Citizenship of the anti-sand mining group from the Community Care Communication Forum of Selok Village. The research location was conducted in Selok Awar-Awar Village, Pasirian Lumajang District, with the research method being a qualitative approach and the case study design referring to the opinion of Robert K. Yin (2003). This research focuses on the impact of illegal sand mining, the real action of anti-mining groups in strengthening the Ecological Citizenship movement, and the growing public awareness of Ecological Citizenship. Data collection techniques applied through observation, interviews, and documentation techniques. The theory used is from Antony Gidens, where the agent is the antimining group, the structure is the community. The results of this study indicate that the role of anti-mining groups, as well as policy support from the local government and concrete actions of anti-mining groups in fighting for the rights to the environment of the community in Selok Awar-Awar village produces duality as evidenced by good cooperation between agents and structures so that mines can be closed, such as through strengthening Ecological Citizenship activities by making (1) Clean, Beautiful, Healthy and Safe (BISA) Movement, (2) Disseminating information to the public to stop sand mining xiii activities completely using a humanitarian approach, (3) Conducting Environmental Education and Campaigns together with the community at the Balai, (4) Conduct studies and determine targets and targets where the damage is the worst and how to deal with it, (5) Plant 6000 mangrove tree seedlings and 1000 sea cypress seeds on the Watu Pecak coast and the southern coast of Lumajang, (6) Conduct mine closures and legal advocacy to Tosan, Salim Kancil. Keywords: ecological citizenship, Mining impact, the role of antimining groups.